Dental Caries and Molar Incisor Hypomineralization prevalence among school children's in Kavrepalanchowk district,Nepal - Prajapati, Dilip; Gurung, Sony; Khoju, Rasik; Bhattarai, Maria (Journal of College of Medical Sciences-Nepal, 2025)
Dental caries and molar incisor hypomineralization (MIH) are common oral conditions in children, affecting quality of life, school performance, and self-esteem. These conditions remain prevalent in low- and middle-income countries even though some efforts are being done. Objective: To determine the prevalence of dental caries and molar incisor hypomineralization (MIH) among school children in Kavrepalanchowk District, Nepal. Methods: A cross-sectional study was conducted involving 622 students from two purposively selected schools. Oral examinations were performed by calibrated dentists using WHO 2013 criteria for dental caries and European Academy of Pediatric Dentistry criteria for MIH. Data were analyzed using descriptive statistics, chi square test and Spearman's rank correlation coefficient Results: Overall, 61.3% of children have dental caries in primary dentition (dmft) and 50.5 % in Permanent dentition (DMFT). Mean dmft score was 3.16 ± 3.40 and mean DMFT was 1.34 ± 1.80. MIH affected 11.7% of molars and 15.3% of incisors, most commonly the maxillary central incisors. Children with molar MIH were 4.9 times more likely to have incisor MIH (p < 0.001). Fluorosis prevalence was low (4.3%). Intervention urgency indicated that 82.2% required prompt treatment, and 5.1% required immediate care. Conclusion: Dental caries remains highly prevalent in this population, with the majority requiring urgent treatment. MIH serves as a significant risk indicator for caries susceptibility. These findings highlight the necessity for targeted, school-based preventive and curative oral health programs.